Evaluation of the West Papua Central Statistics Agency Website Quality Using the WebQUAL 4.0 Method - Edi Meidika; Marlinda Sanglise; Alex De Kweldju (Universitas Islam Raden Rahmat, Malang, 2025)
As the official statistical data provider in Indonesia, BPS always innovates to provide better services to the community. By utilizing information technology, BPS has presented various online services such as websites. This research aims to evaluate the quality of the West Papua BPS website using the webqual 4.0 method. The WebQUAL process involves measuring user perceptions of a website's quality based on three primary dimensions: Usability, Information Quality, and Service Quality. The flow of this research includes planning, data collection and data analysis. This study used 139 respondents. Based on the results of the analysis that has been done, the results of the hypothesis can be concluded that the three dimensions of Usabilitiy, Information Quality and Service Quality are in the category (Accepted) where users feel fast with the quality of the West Papua BPS website.